Carbon-13 Nuclear Magnetic Resonance Study of Metabolism of Propionate by Escherichia coli - London, Robert E. (American Society for Microbiology, 1999)
We have evaluated the use of [1,2-(13)C(2)]propionate for the analysis of propionic acid metabolism, based on the ability to distinguish between the methylcitrate and methylmalonate pathways. Studies using propionate-adapted Escherichia coli MG1655 cells were performed. Preservation of the (13)C-(13)C-(12)C carbon skeleton in labeled alanine and alanine-containing peptides involved in cell wall recycling is indicative of the direct formation of pyruvate from propionate via the methylcitrate cycle, the enzymes of which have recently been demonstrated in E. coli. Additionally, formation of (13)C-labeled formate from pyruvate by the action of pyruvate-formate lyase is also consistent with the labeling of pyruvate C-1. Carboxylation of the labeled pyruvate leads to formation of [1,2-(13)C(2)]oxaloacetate and to multiply labeled glutamate and succinate isotopomers, also consistent with the flux through the methylcitrate pathway, followed by the tricarboxylic acid (TCA) cycle. Additional labeling of TCA intermediates arises due to the formation of [1-(13)C]acetyl coenzyme A from the labeled pyruvate, formed via pyruvate-formate lyase. Labeling patterns in trehalose and glycine are also interpreted in terms of the above pathways. The information derived from the [1,2-(13)C(2)]propionate label is contrasted with information which can be derived from singly or triply labeled propionate and shown to be more useful for distinguishing the different propionate utilization pathways via nuclear magnetic resonance analysis.